2016
DOI: 10.1177/1942602x15618644
|View full text |Cite
|
Sign up to set email alerts
|

Framework for 21st Century School Nursing Practice

Abstract: The National Association of School Nurses (NASN) developed the Framework for 21st Century School Nursing Practice to reflect current school nurse practice. The Framework of practice was introduced in June 2015, and feedback was requested and obtained from practicing school nurses in a variety of ways. The final version of the Framework is introduced in this article. This article updates (and replaces) the articles in the July 2015 NASN School Nurse related to the Framework. Central to the Framework is student-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(69 citation statements)
references
References 22 publications
5
64
0
Order By: Relevance
“…According to the National Association of School Nurses, (NASN), school nurses are required to conduct screenings, referrals, and follow-up activities in schools as part of their role to provide secondary prevention services for health concerns that can be detected early and treated in a timely manner [18]. A systemic review of role and impact of school nurses reported that vision screening and referrals provided as part of health promotion and disease prevention efforts, were some of the most promising services provided by school nurses in American elementary schools and approximately 66% of referrals to school nurses were for screening [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Association of School Nurses, (NASN), school nurses are required to conduct screenings, referrals, and follow-up activities in schools as part of their role to provide secondary prevention services for health concerns that can be detected early and treated in a timely manner [18]. A systemic review of role and impact of school nurses reported that vision screening and referrals provided as part of health promotion and disease prevention efforts, were some of the most promising services provided by school nurses in American elementary schools and approximately 66% of referrals to school nurses were for screening [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly evidenced in numerous national and international research reports and studies (Sherriff et al., ; Attwood & Smith, ; Carroll, Lloyd‐Jones, Cooke, & Owen, ; Hayter, Owen, & Cooke, ; Owen et al., ). In England, school nurses are qualified nurses with specialist training in the public health needs of school‐aged children and young people (Department of Health, ; Jenkins, ; Maughan, Bobo, Butler, Schantz, & Schoessler, ). The “School Health Service” aims to provide programmes and interventions to prevent inequalities, as well as promote and support healthy outcomes for children and young people in educational settings (Department of Health (DH), , ; Public Health England (PHE), , ).…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, school nurses work in public schools to provide health education, surveillance, and clinical services and to participate in setting-oriented public health and health promotion programs [20,21]. Specially trained nurses can conduct individualized and population-based health education, health promotion and health literacy enhancement for different target groups within the school setting [22].…”
Section: Introductionmentioning
confidence: 99%
“…Effective school nurses are highly trained professionals. They have a wide range of clinical, social, and educative competencies, combine nursing expertise, trustworthiness, presence and discretion, and can act as an advocate for children's health concerns [18,21,26]. Compared with teachers, nurses do not assess learning achievements and therefore are more readily able to demonstrate "empathy, compassion, nurturance and uncritical acceptance" [27].…”
Section: Introductionmentioning
confidence: 99%